Uma abordagem prática sobre cooperativas utilizando sistema DEA - Silveira, Márcio José da (2020)
This work aims at an approach on the financial efficiency of cooperatives in the Brazilian scenario, based on the validity and impact of the theme due to the need to seek analyzes that support possibilities to combat the excessive concentration of capital and volume of operations that occurs in the national financial market through increasing participation of credit unions as a means of accessing financial conditions that do not correspond to the practices of the conventional financial system. Such expression and importance occur in view of the growing scenario of the joining of members with common objectives and little access to conventional credit supply conditions, and such cooperatives start to supply needs for the distribution of such conditions, considering better possibilities of accessing credit and geographical capillarity. Considering their social role and the aspects that are particular to them, the norms are directed so that their operation is within the BACEN norms and guarantees legitimacy and clarity in the relations between its participants, interests and how they interact with each other and with the market. brief introduction of its historical construction and economic importance, mainly in cultures that counterpoint the Brazilian scenario, to explain how such a financial system gained space among the population and today has itsown characteristics and laws that regulate its socioeconomic impact.From the brief contemplation of the definition of credit unions in Brazil, their history of constitution, evaluation of the evolution of the norms for them to operate, as a background ofthe current scenario. The work aims to use the Data Envelopment Analysis (DEA) methodology to analyze the Decision Making Units (DMU's in English), as developed in the literature on the topic, in the form of cooperatives that deliver their information to the Central Bank of Brazil. Brazil, an official institution to regulate its financial operations, to measure its efficiency in view of its primary objectives.The structure of this efficiency analysis will be structured as follows, i) introduction: where the contextualization of the essay's significance for the context will be made; ii) explanation of the DEA methodology and its variables; iii) description of the -9 -database used; iv) literature review and support on the DMU’s selected for the work; v) analysis of results and comparisons with the bibliography used; vi) conclusions on the elucidated -